A comparison of outcomes between Syrian and Turkish patients with traumatic brain injury admitted to intensive care in Gaziantep, Turkey, two border sharing countries (Annals of Medical Research, 2021)
Aim: The aim of this study was to analyze the outcomes of Syrian patients with serious TBI admitted alive in intensive care units (ICUs) and to compare their results with Turkish patients.As a direct consequence of the ongoing civil war, Syrian patients with severe traumatic brain injury (TBI) have been receiving neurosurgical intervention in Turkey. Material and Methods: The study was approved by the Institutional Review Board, and written informed consent was obtained from patientsfamilies prior to participation. The study sample consisted of 44 Syrianand 42 Turkish TBI patients in ICUs in Gaziantep, the city which hosts the most Syrian refugees. Medical records of Syrian patients were compared with those of Turkish patients in terms of age, gender, American Society of Anesthesiologist (ASA) scores, mechanism of injury, neurological status (Glasgow Coma Score) [GCS] on admission, surgical methods, postoperative complicationsmorbidity and mortality rates.Results: Totally 25% of Syrian patients were admitted to ICUs for gunshot wounds while 59.5% of Turkish patients were admitted to ICUs due to traffic accident traumas. During hospitalization, factors associated with mortality were low on admission (GCS 8). Of these patients, 79.5% of Syrian and 83.3% of Turkish patients underwent craniotomy and hematoma evacuation. The mortality rates were 63.6% and 64.3% in Syrian and Turkish patients, respectively.Conclusion: There was no significant difference in mortality rates between the two populations. Determining factors that affect mortality can improve the management of TBI patients in ICUs. Results show that prevention is the only available approach.
Keywords: Complications; intensive care unit (ICU); mortality; refugees; Traumatic Brain Injury (TBI)